The development of leadership through islamic education: An empirical inquiry into religiosity and the styles of educational leadership experienced - Imran Hussain Khan Suddahazai (International Journal of Education and Learning, 2021)
The research undertaken sought to address a critical vacuity within contemporary Muslim scholarship on 'educational leadership. The empirical investigation explored the relationship between the formation of 'Religiosity' and the styles of 'Educational Leadership' as experienced by graduates of Muslim Institutes of Higher Education in the UK (MIHEUK). The study was conducted via a single case design with embedded units of analysis. The instruments utilized for data collection were the Muslim Subjectivity Interview Schedule (MSIS), Semi- Structured Interviews (SSI), and Focus Group Discussions (FGD). The data was analyzed to deduce the participants' mode of subjectivity by adopting an established criterion developed by Sahin. The study concluded that the educational leadership' styles of Muslim educators working within traditional and hybrid MIHEUK influenced modes of 'religiosity' and 'subjectivity' of Muslim students.